THE IMPACT OF THE INDONESIAN GOVERNMENT TRANSITION ON THE BUSINESS COMMUNICATION PROCESS IN THE INTERNATIONAL TRADE SECTOR - Wulandari, Tine Agustin; Purwaningwulan, Melly Maulin; Anggaswari, Niluh Ayu; Gosh, Sweta (ASPIRATION Journal, 2025)
The transition of the Indonesian government has significantly impacted the business communication process in the international trade sector. This article explores how new policies during new government transition influence international trade dynamics. Furthermore, this research identifies key challenges in the business communication process, including regulatory uncertainties, intercultural communication differences, and adaptation to technological and diplomatic language shifts. Nevertheless, the transition also presents major opportunities, the opening of new markets, the strengthening of economic diplomacy, and the increased use of digital platforms in business communication. This research concludes that a deep understanding of new policies and adaptive business communication are essential to maintain international trade relations amidst governmental changes. The issue of the new Indonesian government transition is the novelty of this research. It is recommended to conduct further research related to the perception of foreign investors on Indonesian government transition and communication reliability.